Analysis of the level of expression of pancytokeratins in epithelial and granulocellular tumors of the ovaries - Savchenko O.A.; Shponka I.S. (Medičnì Perspektivi, 2018)
Differential diagnosis of ovarian neoplasms is carried out among groups of epithelial and granulocellular tumors and remains an actual problem of oncogynecology. In general, epithelial tumors occur (up to 60%), but granulocellular cell tumors account for up to 5% of all ovarian neoplasia. Materials and methods. A retrospective study of 43 observations of ovarian tumor lesions over the period of January-December 2017 was conducted in the work. The aim of the study was to analyze the complex of morphological and immunohistochemical characteristics of Cytokeratin, Pan AE1 / AE3 - negative phenotypes and Cytokeratin, Pan AE1 / AE3 - positive phenotypes of ovarian neoplasia to improve diagnostic algorithms. Results. The phenotype of epithelial ovarian tumors in 100% of observations corresponds to pancytokeratin Cytokeratin, Pan AE1 / AE3 "+", in its turn the phenotype of granulocellular tumors basically responded to expression of the Cytokeratin marker, Pan AE1 / AE3 "-" in 62.5%; and the variant in the part of the cells "+" / "-" Cytokeratin, Pan AE1 / AE3 was found in 37.5% of granulocellular tumors, regardless of their malignant potential. Thus, granulocellular tumors have variable expression of the Cytokeratin marker, Pan AE1 / AE3 and require the inclusion of other diagnostic IGH markers in the primary panel.